Antifungal Susceptibility Testing to Determine Mic of Amphotericin B, Fluconazole and Ketoconazole Against Ocular Fungal Infection - Mitesh H. Patel; Avani M. Patel; Sachin M. Patel; Govind L Ninama; Kamlesh R. Patel; Bharti C. Lavingia (Medsci Publications, 2011)
Purpose:  To standardize In-vitro antifungal susceptibility testing by agar dilution method to find out minimum inhibitory concentration (MIC) of Amphotericin B, fluconazole and ketoconazole against ocular fungal isolates. Methods: A total of 90 isolates (25 yeast & 65 filamentous fungi) were included. The drugs were added in serial double dilution in medium containing yeast nitrogen base. The MIC was determined by inhibition of visible growth on lowest concentration of drug containing media as comparing with visible growth on drug free media. Results: Out of 25 yeast isolates, all are sensitive to Amphotericin B, 8 % & 12 % are resistant to Fluconazole & ketoconazole respectively. Out of 65 Filamentous fungi, 3 %, 20 % & 28 % are resistant to Amphotericin B, Fluconazole & Ketoconazole respectively. Conclusion: The methodology used in study is user's friendly, reliable & cost effective.